Prospects for Application of Nanotechnology in Marine Industries: A Brief Review - Salmasi, Arian; Abraham, John; Salmasi, Farzin (Innovations in Science and Technology Vol. 4, 2022)
The advent of nanotechnology is an advancement that represents a fundamental change that will lead to the development of materials and tools in the future. The possibility of using nano-building blocks in size and composition is revolutionizing material science. Currently there are many ongoing studies of nanotechnology, its applications, benefits, and future prospects. In the marine industry, which includes a wide range of industries such as shipbuilding, submarines, and offshore platforms, nanotechnology is providing many uses. In fact, nanotechnology has valuable applications in various sectors of the marine industry where it can revolutionize the marine industry. Studies have shown that nanoparticles added to fuel can reduce fuel consumption in diesel engines and can reduce pollutants. The addition of these nanoparticles to the fuel leads to the decomposition of burnt hydrocarbons and soot, which improves efficiency. Consequently, the amount of soot, HC and CO decreases. The results of physical testing have confirmed the role of nanoparticles for increasing efficiency and reducing pollution. In this study, some applications of nanotechnology in the marine industry are discussed. For example, nanoparticle matrices in battery electrodes can drastically increase their ability to store lithium ions, increasing the storage density of the battery. Graphene can be used as a self-lubricating solid or as an additive for lubricating oils. Application of nanotechnology for the fabrication of cellular ceramic can improve its thermal stability and mechanical strength. Overall, nanotechnologies seem to have huge potential in areas as diverse as drug development, water decontamination, information and communication infrastructures, and the production of stronger, lighter and perfect nanomaterials. The benefits of nanotechnology to marine applications is no less significant.